2015
DOI: 10.14419/ijans.v4i1.3858
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perceptions about child abuse

Abstract: Background: Despite the efforts to protect children around the world, child abuse and neglect remain serious and global problems. In Palestine, child abuse is hidden under the community culture, does not appear in the Ministry of Health official reports, and little is known about nurses’ perceptions towards this phenomenon.Objectives: To identify nurses’ perceptions about child abuse definition, whether they faced such cases during their work, and how they managed them.Methods: Data were collected using de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, since perception of maltreatment is subjective, therefore differing across cultural, racial, ethnic backgrounds, and developmental stages (Ashton, 2010;Shanalingigwa, 2009), it is of particular interest to broaden the understanding of perceptions of maltreatment among adults and youth. For example, Saifan, Alrimawi, and Bashayreh (2015), who examined Palestinian nurses' perceptions of child maltreatment, reported that most nurses did not know how to handle with child abuse survivors effectively and found it hard to differentiate between violent physical and psychological disciplinary practices and child abuse. Toros and Tiirik (2014), who studied teachers' ability to identify abused children, found that although teachers understand the meaning of "child in need" they failed in identifying emotional neglect and abuse.…”
Section: Introductionmentioning
confidence: 99%
“…However, since perception of maltreatment is subjective, therefore differing across cultural, racial, ethnic backgrounds, and developmental stages (Ashton, 2010;Shanalingigwa, 2009), it is of particular interest to broaden the understanding of perceptions of maltreatment among adults and youth. For example, Saifan, Alrimawi, and Bashayreh (2015), who examined Palestinian nurses' perceptions of child maltreatment, reported that most nurses did not know how to handle with child abuse survivors effectively and found it hard to differentiate between violent physical and psychological disciplinary practices and child abuse. Toros and Tiirik (2014), who studied teachers' ability to identify abused children, found that although teachers understand the meaning of "child in need" they failed in identifying emotional neglect and abuse.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] Saifan ↱ et al . [ 28 ] also found that nurses tried to manage these situations. Nurses feel empathy with their children and are concerned about their future.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 34 ] Furthermore, Saifan et al . [ 28 ] reported that most of the health care providers who directly deal with CVVs have had no training regarding CVVs. Borimnejad and Fomani[ 4 ] have also reported the need for broadening nurses' knowledge about child violence and developing clear guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most developing countries, healthcare providers are not trained in child abuse expectations within their scope of practice and are unsure of what their primary responsibility is as mandatory reporters (Jordan and Steelman, 2015). Lack of health care providers expertise in child abuse could be because of insufficient training and knowledge on child abuse, and a lack of standardized guidelines for reporting these cases (Saifan, Alrimawi and Bashaireh, 2015).…”
Section: Role Of Health Care Providersmentioning
confidence: 99%